Evaluation of a clinically practical, ERP-based neurometric battery: Application to age-related changes in brain function. Issue 5 (May 2016) - Kieffaber, Paul D.; Okhravi, Hamid R.; Hershaw, Jamie N.; Cunningham, Emily C.
Highlights: A clinically practical ERP protocol for neurometric profiling. Detecting age-related changes in brain function in high-functioning older adults. Healthy brain aging is associated with altered visual and sensory memory. Abstract: Objective: Event-related potentials (ERPs) show promise as markers of neurocognitive dysfunction, but conventional recording procedures render measurement of many ERP-based neurometrics clinically impractical. The purpose of this work was (a) to develop a brief neurometric battery capable of eliciting a broad profile of ERPs in a single, clinically practical recording session, and (b) to evaluate the sensitivity of this neurometric profile to age-related changes in brain function. Methods: Nested auditory stimuli were interleaved with visual stimuli to create a 20-min battery designed to elicit at least eight ERP components representing multiple sensory, perceptual, and cognitive processes (Frequency & Gap MMN, P50, P3, vMMN, C1, N2pc, and ERN). Data were recorded from 21 younger and 21 high-functioning older adults. Results: Significant multivariate differences were observed between ERP profiles of younger and older adults. Metrics derived from ERP profiles could be used to classify individuals into age groups with a jackknifed classification accuracy of 78.6%. Conclusions: Results support the utility of this design for neurometric profiling in clinical settings. Significance: This study demonstrates a method for measuring a broad profile of ERP-based neurometrics in a single, brief recording session. These markers may be used individually or in combination to characterize/classify patterns of sensory and/or perceptual brain function in clinical populations.